ANALISIS BIAYA PEREMAJAAN PERKEBUNAN KELAPA SAWIT PLASMA POLA PIR-BUN DI KECAMATAN KOTO GASIB KABUPATEN SIAK - Romadani Siregar; Saiful Hadi; Sakti Hutabarat (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
This study aims to calculate the cost of replanting oil palm plants. This research was conducted in KeranjiGuguh Village and TasikSeminai Village, Koto GasibSubdistrict, Siak Regency, Riau Province, the selection of this location was based on the consideration that in these two villages the majority of the population cultivated oil palm plantations with an average plant age of 39 years. Respondents in this study were oil palm planters in KeranjiGuguh Village and TasikSeminai Village, the sampling technique used the Simple Random Sampling method, the number of samples taken was 10 farmers and 7 experts from each village. The analysis used in this research is descriptive analysis. The results of the study explain that the total cost of P0-P3 is Rp. 52,960,661/ha. While the size of the loan provided by Bank Mandiri is Rp. 87,700,000. If the land for replanting is 2 ha for each farmer, then the total cost required is Rp. 105,921,322 and the planters still have to find a lack of funds of Rp. 18,221,322. The use of the highest cost is in the activity of planting oil palm seeds, which is Rp. 7,318,500/ha and the lowest cost is for land preparation activities, which is Rp. 88,331/haKeywords: Rejuvenation, Palm Oil, Rejuvenation Cost